Programa escola em casa: o papel das professoras dos anos iniciais no processo do ensino remoto emergencial na rede municipal de ensino de Uberlândia (2020/2021) - Moraes, Leordina Ferreira Tristão (2022)
This research has as its theme teaching in the process of emergency remote teaching -ERE - in the municipal education network of Uberlândia, during the Covid-19 Pandemic. Your problem will be to understand the role and function of teachers in the early years of Elementary School 1 during the ERE in the context of the elaboration and implementation of the Escola em Casa Program in the years 2020 and 2021, in accordance with the regulations and resolutions of the Municipal Secretary of Education (SME). It seeks to identify how the organization of the pedagogical work was planned in the ERE; to understand which teaching functions were defined and distributed in the planning of the ERE by the SME of Uberlândia and to analyze how the roles of teachers in the development process of the ERE of the municipal network of Uberlândia were delineated/considered, formulated and reformulated. This is a qualitative research, based on a bibliographical review of existing studies, as well as documentary research (documents, laws, decrees, regulations and other legislation produced in the pandemic). The main authors that are part of the theoretical framework are: Nóvoa, Alvim (2021, 2022) regarding school tradition; Veiga (2008), Campos (2007), Masetto (2003) on the class, autonomy and teaching work; polyteaching in Mill (2006, 2015, 2014); Peixoto (2015, 2106, 2020) with pedagogical mediation in the dialectical perspective and the relationships between social subjects and technical objects; emergency remote teaching in De Figueiredo Souza e Ferreira (2020) , Hodges, Moore, Lockee (2020), Guimarães, (2021) , Oliveira and Pochmann (2020); Lakatos (1990), Kripka, Scheller, Bonotto (2015) and documentary research; Bravo (1991) on research sources. As a result, it is highlighted that the documents produced by the managers of the SME of Uberlândia during the pandemic ignore the reality experienced by the less favored classes of students in vulnerable situations, in addition to curtailing authorship and teaching autonomy in the process of organizing the pedagogical work. In which educational reformers are increasingly present.